Diseño y construcción de una máquina trilladora de amaranto, para el campus de Salache en la universidad técnica de Cotopaxi - Iza Niza, Johnny Javier (2019)
The technological proposal shown below was made for the Andean grains project of the Technical University of Cotopaxi, in which the implementation of a threshing machine was formulated to motivate and help in the investigation processes of the cultivation of the amaranth plant carried out by students in the campus of Salache. To begin to develop the technological proposal, an investigation was carried out on the Amaranth and the main parameters required to have the grain at the moment of entering the plant to the machine, as they are their degree of maturity and the percentage of humidity, then we proceeded to a design context using tools such as the house of QFD quality which is a decision making methodology which translates the customer's requirements into design parameters and by engineering criterion gives solution to these, another tool that was used was the method of Finite Element Analysis FEM-FEA, using the ANSYS Structural Analysis software, in which the conditions to which the element will be subjected are configured, to obtain data that directly influence the design of the machine. The elements tested are the axes of transmission of the threshing drum, where the efforts and the loads to which they are subjected are simulated to determine the problems that directly affect them. The mechanical stresses of tension, bending, torsion and the safety factor were determined by means of a structural safety test to guarantee the useful life. Finally, the amaranth threshing machine with a capacity of 100 Kg per Hour was built, complying with the design and manufacturing requirements using the previously analyzed materials so that their operation is adequate and thus a relatively low total cost was generated in comparison with the existing machines in the market.